Neonatal Bladder Inflammation Results in Adult Female Mouse Phenotype With Increased Frequency and Nociceptive Responses to Bladder Filling - Clodfelder-Miller, Buffie; Ness, Timothy J.; DeBerry, Jennifer J. (Frontiers in Systems Neuroscience, 2022)
Bladder pain and hypersensitivity to bladder filling are clinically common, but animal models examining syndromes with these features are limited. A rat model of bladder hypersensitivity produced by neonatal bladder inflammation (NBI) has been reported to have many of the clinical features of bladder pain syndromes. The present study sought to determine whether similar hypersensitivity might be induced by NBI in mice. Female C57BL6/J mice had NBI induced on postnatal days P12-14 by the intravesical administration of zymosan. As adults (12-14 weeks of age), the mice were examined for hypersensitivity of their bladders as: spontaneous voiding and evoked cystometrograms at baseline, and visceromotor responses (VMRs) to urinary bladder distension (UBD) following a secondary insult (either repeated bladder inflammation or acute stress induced by footshock). Mice that experienced NBI demonstrated hypersensitivity, when compared with control mice, manifested as increased spontaneous voiding, increased frequency of evoked voids during intravesical saline infusion, and increased vigor of VMRs to UBD following either acute bladder inflammation or acute stress. This recapitulates the hallmark features of clinical painful bladder disorders and suggest utility of this murine model for the study of these disorders while allowing methodological expansion into well-established genetic and immunological models.